Robust performance of soft real-time networked control systems with data dropouts - Qiang Ling; Lemmon, M.D. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
This paper derives the power spectral density (PSD) of the output generated by a discrete-time feedback control system in which feedback measurements are dropped with a known probability, /spl epsi/. This class of systems is a model for soft real-time control systems in which the feedback path is implemented on a nondeterministic computer network. The PSD computed in this paper is a function of the dropout probability. The dropout probability is taken as a measure of the network quality of service (QoS). Based on the derived PSD, the power semi-norm of the output is predicted. So a direct way of linking control system performance(as measured by the power semi-norm of the output) to the network's QoS (as measured by the dropout probability) is provided.